Study of air void topology of asphalt with focus on air void constrictions – a review and research approach. (1st June 2021) - Schuck, Barbara; Teutsch, Tim; Alber, Stefan; Ressel, Wolfram; Steeb, Holger; Ruf, Matthias
Abstract : The aim of this paper is to show the complexity of studying air void topology by giving an in-depth literature review. Factors defining air void structure are presented and relationships and correlations are highlighted. The hydraulic conductivity of asphalt is then put in context of air void analyses. A new approach to distinguish constrictions in the air void matrix is introduced. The bigger air voids represent the drainage (volumetric) capacity. The constrictions, on the other hand, have a direct influence on hydraulic conductivity, as clogging could easily diminish or eliminate them. This approach should improve the meaningfulness of studies analysing air void characteristics. With X-ray CT scans, an analysis of the middle section of two artificially soiled porous asphalt cores is then presented. As expected, approximately homogeneous behaviour of air voids as well as constrictions can be observed.